Smoke interacts with fire history to stimulate soil seed bank germination in Mediterranean woodlands. (7th December 2018) - Manela, Neta; Dagon, Ella; Semesh, Hagai; Ovadia, Ofer
Abstract: Aims: Fire has important consequences on vegetation dynamics. In fire-prone areas, natural selection favors plant species, characterized by a large soil seed bank, and that their germination is stimulated by fire. Although seed germination stimulated by fire heat is common in the eastern Mediterranean Basin, only little is known about germination stimulation by smoke. We examined the interactive effect of aerosol smoke and fire history on the germinable soil seed bank (GSSB) community in eastern Mediterranean woodlands. Methods: We collected soil samples from sites that have been subjected to different fire frequencies during the last four decades and exposed them to aerosol smoke, with or without watering. By documenting the seed germination patterns characterizing these samples, we could test for changes in the abundance and richness of the germinable seeds in the soil. Important Findings: Total GSSB density was higher in sites that were burned more frequently during the last four decades. Exposure to aerosol smoke increased the GSSB density, and this pattern was more pronounced in samples originating from sites burned more frequently, as well as among annual species. Notably, exposing wet samples to aerosol smoke caused a significant reduction in GSSB density and richness. These results highlight the importance of exploring germination responses using intact soil samples, rather than synthetic seed communities. Moreover, our findings emphasize the important role smoke plays in shaping post-fire succession processes in the Mediterranean Basin, mainly by stimulating the germination of annual species.